49.4k views
4 votes
If b-a = c-b = d-c, what expression is equal to d-b?

User Rori
by
5.2k points

1 Answer

1 vote

Answer:

c - a

Explanation:

Given that b-a = c-b = d-c, to find the expression equal to d-b, separate the equations in the manner below

b-a = d-c

and

c-b = d-c

From the first equation, subtract b from both sides such that

b - a - b = d - c -b

-a = d-c -b

Add c to both sides such that

c - a = d-c -b + c

c - a = d - b

Hence d - b is equal to c - a

User Nouman Zaka
by
5.3k points